Summerhill: “SEEDS” of democracy - O'Rourke, Deb (Revista Hipótese, 2018)
In Canada and the US, A. S. Neill’s 1960 book on Summerhill inspired the FreeSchool Movement, in which hundreds of grassroots schools were created by parents,teachers and students. In Canada, public alternative schools were created to ensure that alleconomic classes could have access to different education models, but very few free schoolshave survived the systemic pressures. ALPHA Alternative School includes parents in thedemocratic partnership and relies on their advocacy. The author sees Summerhill as a vitalrole-model, not only for education that fosters “strong individuals and community persons”, but for feisty school communities struggling to survive and, in the process, draw their nationsfurther along the spectrum from idealized to actualized democracy.
Keywords: Neill; Summerhill; Free school; Alternative school; Democratic; ALPHA Alternative School, Toronto, Canada